(untitled) - United States Department of Agriculture; Natural Resources Conservation Service (Lincoln, 1995)
Contents: Introduction; samplling methodology; soil survey laboratory data reports; primary characterization data sheet; supplementary characterization data sheet.
Keywords: Soil surveys,Thổ nhưỡng